Efficacy and safety of a fixed-dose combination of nimesulide/pantoprazole compared to naproxen/esomeprazole for pain relief in patients with osteoarticular diseases and dyspeptic symptoms - Scheinberg M; Pott Júnior H; Macêdo EA; Bocchi de Oliveira MF; Ecclissato C; Amazonas RB (Dove Medical Press, 2018)
Morton Scheinberg,1 Henrique Pott Júnior,2 Eduardo de Almeida Macêdo,2 Monalisa Fernanda Bocchi de Oliveira,2 Christina Ecclissato,2 Roberto Bleuel Amazonas2 1Clinical Research Center Hospital AACD, Hospital Israelita Albert Einstein, São Paulo, Brazil; 2Medical Affairs Department, EMS Pharma Inc., Hortolândia, Brazil Purpose: This study investigated the safety and efficacy of fixed-dose combination tablets of naproxen/esomeprazole magnesium and nimesulide/pantoprazole to determine if both regimens are equally suited to relieve pain in patients with osteoarticular diseases and dyspeptic symptoms. Methods: Patients were randomly assigned to receive either nimesulide/pantoprazole (100 mg/20 mg) twice daily or naproxen/esomeprazole magnesium (500 mg/20 mg) twice daily for 14 days. The primary endpoint was defined as the mean change in modified Western Ontario and McMaster Universities Osteoarthritis Index pain subscale. Secondary endpoints were mean visual analog scale score of dyspeptic symptoms (nausea, abdominal discomfort/pain, epigastric burning, postprandial fullness), mean visual analog scale score of individual dyspeptic symptoms, and individual score of dyspeptic symptoms according to patient diary. This study is registered at ClinicalTrials.gov: NCT01670552. Results: A total of 490 patients were enrolled and randomized, and 399 completed treatment (naproxen/esomeprazole, n=201; nimesulide/pantoprazole, n=198). The difference in mean change in the modified Western Ontario and McMaster Universities Osteoarthritis Index pain score after 7 days of treatment between the two treatment groups was 2.33 mm (95% CI, -1.22 to 5.89 mm). After 14 days of therapy, the difference was 0.45 mm (95% CI, -3.29 to 4.19 mm). The most common adverse events in the pooled group were abdominal discomfort, abdominal distention, dyspepsia, and nausea, but none of these was deemed to be clinically meaningful. Conclusion: The present study demonstrated noninferiority of a 14-day regimen with a fixed-dose combination of nimesulide/pantoprazole compared to naproxen/esomeprazole for the treatment of osteoarticular pain. Keywords: osteoarticular diseases, naproxen, esomeprazole, nimesulide, pantoprazole, randomized controlled trial